Transient association of MCM complex proteins with the nuclear matrix during initiation of mammalian DNA replication - Hesketh, Emma L (Cell Cycle, 2015)
The minichromosome maintenance complex (MCM2-7) is the putative DNA helicase in eukaryotes, and essential for DNA replication. By applying serial extractions to mammalian cells synchronized by release from quiescence, we reveal dynamic changes to the sub-nuclear compartmentalization of MCM2 as cells pass through late G1 and early S phase, identifying a brief window when MCM2 becomes transiently attached to the nuclear-matrix. The data distinguish 3 states that correspond to loose association with chromatin prior to DNA replication, transient highly stable binding to the nuclear-matrix coincident with initiation, and a post-initiation phase when MCM2 remains tightly associated with chromatin but not the nuclear-matrix. The data suggests that functional MCM complex loading takes place at the nuclear-matrix.